(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
On 2019 and 2022, a year before and after the Covid-19 pandemic, indicates fluctuating conditions in net profit and increasement in operational costs of F&B Department Hotel Indigo Bali Seminyak Beach. This writing aims to present a solution to reduce operational costs and increase the percentage of net profit. The method used is assistance in implementing cost leadership and the EOQ (Economic Order Quantity) approach in price break cases. By implementing cost leadership strategy and EOQ (Economic Order Quantity) in price break cases, the F&B Department of Hotel Indigo Bali Seminyak Beach will get optimal order quantities and the best prices from suppliers, reduce operational costs, and set lower selling prices.